2022
DOI: 10.1136/jnis-2022-019152
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical thrombectomy in ischemic stroke after cardiovascular procedures: a propensity-matched cohort analysis

Abstract: BackgroundStroke after a cardiovascular procedure (CVP) is a devastating complication adversely affecting outcome. Mechanical thrombectomy (MT) has not been investigated systematically in this population.ObjectiveTo carry out a retrospective study in patients undergoing MT for early stroke after CVP, aiming to further characterize this cohort of patients, and to evaluate the efficacy, safety, procedural characteristics, and outcome of MT.MethodsA single-center stroke registry of patients who received MT was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
3
0
0
Order By: Relevance
“…Consistent with previous studies 10 11 24 28 , EVT did not lead to an increase in total intracranial hemorrhage in perioperative AIS patients compared to community-onset AIS patients. However, when hemorrhages with different subtypes according to the Heidelberg hemorrhage classification were considered, there were significantly more perioperative AIS patients with HI1 and PH1 type hemorrhages and subarachnoid hemorrhage than community-onset AIS patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous studies 10 11 24 28 , EVT did not lead to an increase in total intracranial hemorrhage in perioperative AIS patients compared to community-onset AIS patients. However, when hemorrhages with different subtypes according to the Heidelberg hemorrhage classification were considered, there were significantly more perioperative AIS patients with HI1 and PH1 type hemorrhages and subarachnoid hemorrhage than community-onset AIS patients.…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed that the recanalization rate after EVT did not differ between perioperative and community-onset AIS stroke patients, which corroborates previous studies on stroke patients after both cardiovascular and non-cardiovascular surgeries 10 24 . Importantly, the time from symptom onset to groin puncture in our study is shorter in perioperative stroke patients than in community-onset AIS stroke patients (median time, 239 vs. 433 minutes).…”
Section: Discussionsupporting
confidence: 91%
“…We found that higher NIHSS scores were associated with open cardiac surgery, which is consistent with previously published estimates of the NIHSS score after open cardiac surgery (presumably due to higher rates of large-vessel occlusion and comorbid anesthesia or sedation) . We also found that cardiac intervention was associated with lower probability of having an NIHSS score documented.…”
Section: Discussionsupporting
confidence: 90%